2022
DOI: 10.1371/journal.pone.0269112
|View full text |Cite
|
Sign up to set email alerts
|

Association of obstructive sleep apnea and opioids use on adverse health outcomes: A population study of health administrative data

Abstract: Rationale Despite the high prevalence of obstructive sleep apnea (OSA) and concurrent use of opioid therapy, no large-scale population studies have investigated whether opioid use and pre-existing OSA may interact synergistically to increase the risk of adverse health consequences. To address this knowledge gap, we conducted a retrospective cohort study using provincial health administrative data to evaluate whether the combined presence of opioid use and OSA increases the risk of adverse health consequences, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…For example, clinical indications for the opioid prescription and results of the sleep study to identify a specific sleep disorder were not available. However, we showed previously a significantly increased hazard of all-cause mortality, hospitalizations and ED visits associated with opioid prescription vs. not, regardless of SDB presence (Kendzerska et al, 2022). Importantly, we demonstrated a higher prevalence of opioid use with a large proportion on longacting opioids, higher opioid dosages, and on benzodiazepines among adults referred for a sleep disorder assessment than the general population (Kendzerska et al, 2020), suggesting that these individuals are more susceptible to opioid-related adverse health consequences regardless of clinical indications for the opioid prescription or sleep disorder assessment.…”
Section: Figurementioning
confidence: 59%
See 3 more Smart Citations
“…For example, clinical indications for the opioid prescription and results of the sleep study to identify a specific sleep disorder were not available. However, we showed previously a significantly increased hazard of all-cause mortality, hospitalizations and ED visits associated with opioid prescription vs. not, regardless of SDB presence (Kendzerska et al, 2022). Importantly, we demonstrated a higher prevalence of opioid use with a large proportion on longacting opioids, higher opioid dosages, and on benzodiazepines among adults referred for a sleep disorder assessment than the general population (Kendzerska et al, 2020), suggesting that these individuals are more susceptible to opioid-related adverse health consequences regardless of clinical indications for the opioid prescription or sleep disorder assessment.…”
Section: Figurementioning
confidence: 59%
“…Previously, we found that adults referred for a sleep disorder assessment who used prescription opioids had a significantly increased hazard of all-cause mortality, hospitalizations and ED visits compared to non-opioid users, regardless of SDB presence (Kendzerska et al, 2022). We also demonstrated a higher prevalence of opioid use with a large proportion on longacting opioids and higher opioid dosages, and a higher use of benzodiazepines among adults referred for a sleep disorder assessment than the general population (Kendzerska et al, 2020), suggesting that these individuals are more at risk for opioidrelated adverse health consequences.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In a general surgical population, 3 months after surgery, around 7% of patients still use opioids that were initiated for postoperative pain [43]. Use of opioids in patients with OSA is associated with negative long-term health outcomes [44 ▪▪ ] and use of multimodal analgesia and engagement from specialist pain services are key in this patient group.…”
Section: Management Of the Patient With Diagnosed Obstructive Sleep A...mentioning
confidence: 99%